The reflective museum practitioner expanding practice in science museums - Martin, Laura W.; Tran, Lynn Uyen; Ash, Doris (Routledge, Taylor & Francis Group, 2019)
The Reflective Museum Practitioner explores a range of expansive and creative ways in which the concept of "reflective practice "has been applied in the informal STEM (science, technology, engineering, and mathematics) learning environments of museums and zoos. It seeks to demonstrate how such a process can inspire lifelong learning in practitioners, to the benefit of practitioners and visitors alike. Presenting six projects that employed reflective practice, the contributors examine how each project has encouraged and sustained reflection, and the outcomes thereof. The projects cover a wide range of different practitioners--including administrators, scientists, educators, and other front-line and back-room staff--who work at different junctures of their organizations. Collectively, they raise key questions about changing communities of practice in Informal Science Learning institutions. The projects and concept of "reflective practice "are fully defined and contextualized by the editors, who offer in-depth analysis, along with a cultural-historical activity theory framework, for understanding how changes in museum practice unfold in an institutional context. The Reflective Museum Practitioner offers museum professionals insight into "reflective practice, "as practiced by other institutions in their sector, providing practical examples that can be adapted to their needs. It will also be of interest to scholars and students focusing on science museums, or professional practice development in museums.